Development of Flipbook E-Modules of Science for Basic School Students - Hasanah, Qoriatul; Sari, Eka Yuliana (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aims to develop an e-module flipbook as a learning media that directs active students in using technology in the learning process. The research method used is R&D (Research and Development) with the ADDIE development model (Analysis, Design, development, Implementation, and Evaluation). Data collection is carried out by the steps in the development research process from the data that the researcher has obtained, followed by the process of analyzing the research results that have been obtained. The results showed that the E-module Flipbook Science Style Material was said to be valid and able to encourage students' independent learning interest in learning activities, it can be seen from the media expert scoring 95% "Very Valid" validation from material experts with a score of 87.50% "Very valid" and linguist validator score percentage 94% "Very valid". The development of e-modules made by researchers also increased students' independent learning interest from the results of small group trials on seven fourth-grade students at SDN 1 Pucangan, which obtained a percentage score of 85.71%, and large group trials on 14 fourth-grade students at SDN 1 Karanganom obtained a percentage score of 85.96% with the category "very valid".